Awareness regarding self-prevention and response to heatwaves among the residents in several wards and communes in Thua Thien Hue province - Nguyen, Thanh Gia; Hoang, Nguyen Thanh Dat; Nguyen, Van Hiep; Tran, Binh Thang; Le, Dinh Duong; Nguyen, Minh Tu; Dang, Thi Anh Thu (Tạp chí Y Dược Huế, 2025)
Background: Heatwaves pose a threat to public health in Vietnam, and unprecedented heatwaves have been recorded in Thua Thien Hue province over recent years. Objective: This study aimed to examine the knowledge, attitudes, and practices (KAP) regarding self-protection and response to heatwaves among residents in some Thua Thien Hue province communes and investigate their associated factors. Materials and methods: A cross-sectional study involving 500 participants was conducted in March 2024. Multivariate logistic regression analysis was utilized to identify the associated factors. Results: Our findings indicated that the prevalence of heat-related illnesses was 24.2%, while chronic diseases accounted for 41.6%. The proportions of residents demonstrating good knowledge, attitudes, and practices regarding self-protection and responses to heatwaves were 92.0%, 61.2%, and 62.2%, respectively. Factors associated with knowledge regarding prevention and responses to heatwaves included age group, educational background, heat-related illnesses, chronic diseases, nature of work, primary cooling methods, and information sources. Attitudes were influenced by profession, area of residence, financial family status, and knowledge. Factors associated with practices included age group, educational background, area of residence, chronic diseases, nature of work, primary cooling methods, information sources, knowledge, and attitudes (p<0.05). Conclusion: A high proportion of participants demonstrated good knowledge. However, attitudes and practices regarding heat prevention measures were relatively low. Our findings could help reframe and communicate Thua Thien Hue’s heat wave plans in the light of climate change